Clinical features and disturbances of gastrointestinal transit in patients with rapid gastric emptying. Issue 4 (20th January 2020) - Kuwelker, Saatchi; Muthyala, Anjani; O'Connor, Michael; Bharucha, Adil E.
Abstract: Aims: Some patients with upper gastrointestinal symptoms have rapid gastric emptying (GE). We aimed to compare patients with normal and rapid GE and to identify phenotypes among patients with rapid GE. Methods: Among 2798 patients who underwent GE scintigraphy, we compared patients with normal and rapid GE and separately, patients with rapid GE at 1 hour (GE1), 2 hours (GE2), or both (GE12). Results: In 2798 patients, GE was normal (74%), delayed (18%), or rapid (8%). Among 211 patients with rapid GE, patterns were rapid GE1 (48%), 2 hours (17%), or 1 and 2 hours (35%); 42 (20%) had diseases that explain rapid GE. A combination of upper and lower gastrointestinal symptoms (54%) was more common that isolated upper (17%) or lower (28%) gastrointestinal symptoms ( P < .001). Constipation was more prevalent in patients with rapid GE 2 (72%) than rapid GE 1 (47%) or rapid GE12 hours (67%) (P < .05). Among 179 diabetes mellitus (DM) patients, 15% had rapid GE, which was not associated with the DM phenotype. By multivariable analysis, insulin therapy (odds ratio [OR], 0.36; 95% confidence interval [CI], 0.15‐0.88), and weight loss (OR, 0.10; 95% CI, 0.01‐0.78) were associated with a lower risk of rapid than normal GE in DM. Conclusions: Eight percent of patients undergoing scintigraphy had rapid GE, which is most frequently associated with upper and lower gastrointestinal symptoms; constipation is common. Insulin therapy and weight loss were associated with a lower risk of rapid than normal GE in DM patients. Abstract : Eight percent of patients undergoing scintigraphy had rapid gastric emptying at 1, 2, or at 1 and 2 hours. Over 50% of patients have upper and lower GI symptoms; constipation is common. In DM patients, insulin use and weight loss were associated with a lower risk of rapid than normal GE.